2021
DOI: 10.1210/clinem/dgab320
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Neurokinin 3 Receptor Antagonist Fezolinetant for Treatment of Polycystic Ovary Syndrome

Abstract: Context Polycystic ovary syndrome (PCOS), a highly prevalent endocrine disorder characterized by hyperandrogenism, is the leading cause of anovulatory infertility. Objective This proof-of-concept study evaluated clinical efficacy and safety of the neurokinin 3 (NK3) receptor antagonist fezolinetant in PCOS. Design This was a phase 2a, randomized, double-blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…153 No clear changes in circulating estradiol concentrations or ovulatory function were observed in this relatively short-term study. 153 The success of longer-term NK3R antagonism in PCOS remains to be determined. The potential impact of chronic NK3R antagonism on gonadotropin surge generation and ovulation is unknown.…”
Section: P Otential Effi C Ac Y Of Pharmacolog Ic Al Ag Ents Targ E T...mentioning
confidence: 53%
See 2 more Smart Citations
“…153 No clear changes in circulating estradiol concentrations or ovulatory function were observed in this relatively short-term study. 153 The success of longer-term NK3R antagonism in PCOS remains to be determined. The potential impact of chronic NK3R antagonism on gonadotropin surge generation and ovulation is unknown.…”
Section: P Otential Effi C Ac Y Of Pharmacolog Ic Al Ag Ents Targ E T...mentioning
confidence: 53%
“…For example, a study in adults with PCOS suggested that the selective NK3R antagonist pavinetant (formerly MLE4901 and AZD4901) administered at a dose of 80 mg day and LH:FSH ratio by almost 60%. 153 Although LH pulse frequency was not assessed in this study, reductions in LH:FSH ratio and testosterone were sustained for 12 weeks of treatment. 153 No clear changes in circulating estradiol concentrations or ovulatory function were observed in this relatively short-term study.…”
Section: P Otential Effi C Ac Y Of Pharmacolog Ic Al Ag Ents Targ E T...mentioning
confidence: 85%
See 1 more Smart Citation
“…The investigators argued that a 12-week duration of treatment in this trial may be inadequate to change these parameters as positive clinical outcomes in PCOS clinical trials are typically detected after 6-9 months of treatment. 117,123 Taken together, neurokinin receptor antagonism may negate differential hypersecretion of LH (i.e., excessive secretion of LH in comparison to FSH), and by extension, prevent excessive ovarian androgen production, a cardinal feature of PCOS.…”
Section: Postmenopausal Hot Flushesmentioning
confidence: 99%
“…As in other studies, NK3R antagonist treatment resulted in lower LH levels while not affecting those of FSH, thus reducing LH/FSH ratio. Fezolinetant is now in phase 3 development for the treatment of vasomotor symptoms in postmenopausal women 117 …”
Section: Tacr3 and Tac3mentioning
confidence: 99%